2009
DOI: 10.2217/imt.09.32
|View full text |Cite
|
Sign up to set email alerts
|

Separating Graft-Versus-Leukemia From Graft-Versus-Host Disease in Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Routine methods to maximize the graft-versus-leukemia (GvL) activity of allogeneic hematopoietic stem cell transplantation (HSCT) without the detrimental effects of graft-versus-host disease (GvHD) are lacking. Depletion or inhibition of alloreactive T cells is partially effective in preventing GvHD, but usually leads to decreased GvL activity. The current model for the pathophysiology of acute GvHD describes a series of immune pathways that lead to activation of donor T cells and inflammatory cytokines respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(7 citation statements)
references
References 280 publications
(243 reference statements)
0
7
0
Order By: Relevance
“…The descriptions of transplant characteristics, such as donor, race, TBI, nephrotoxic agents, and post-transplant adverse events, such as aGVHD and infection, were inconsistently described as risk factors for the development of AKI 21 23 . Studies had shown that unrelated donors were closely associated with AKI (HR, 6.26; P = 0.042) 20 .It had been reported that transplantation of hematopoietic stem cells from unrelated donors was associated with a significant increase in the risk of infection, severe aGVHD, and organ toxicity 24 29 . Calcineurin inhibitor (CNIs) caused AKI by arteriolar vasoconstriction, reducing kidney perfusion, tubular toxicity, and endothelial injury 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The descriptions of transplant characteristics, such as donor, race, TBI, nephrotoxic agents, and post-transplant adverse events, such as aGVHD and infection, were inconsistently described as risk factors for the development of AKI 21 23 . Studies had shown that unrelated donors were closely associated with AKI (HR, 6.26; P = 0.042) 20 .It had been reported that transplantation of hematopoietic stem cells from unrelated donors was associated with a significant increase in the risk of infection, severe aGVHD, and organ toxicity 24 29 . Calcineurin inhibitor (CNIs) caused AKI by arteriolar vasoconstriction, reducing kidney perfusion, tubular toxicity, and endothelial injury 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines are critical drivers of both GVHD and GVL, and current evidence indicates that different cytokines may play different roles in GVHD vs the GVL effect[ 122 - 133 ]. In a recent study, Tugues et al [ 108 ] used an MHC-mismatched HSCT mouse model and found that donor T cell-derived granulocyte-macrophage colony-stimulating factor (GM-CSF) can drive GVHD pathology by licensing donor-derived phagocytes to produce inflammatory mediators such as IL-1 and reactive oxygen species (ROS).…”
Section: Regulation Of Gvl and Gvhdmentioning
confidence: 99%
“…For example, depletion of ␣␤ T cells and naive T cells decreases GVHD while increasing numbers of ␥␦ or memory T cells, or CD4 ϩ CD25 ϩ regulatory T cells (Tregs) enhance GVL and/or suppress GVHD. 10 T cells are no longer thought to be the only immune cells responsible for GVL; donor-derived natural killer (NK) and dendritic (DC) cells also playing key roles. 11,12 Early efforts to identify the timing and the immunologic mechanisms responsible for GVHD focused on augmenting the GVL response through donor lymphocyte infusions.…”
Section: Graft Versus Leukemiamentioning
confidence: 99%